Characterisation of Early Positive mcr-1 Resistance Gene and Plasmidome in Escherichia coli Pathogenic Strains Associated with Variable Phylogroups under Colistin Selection - Guerrino Macori; Scott V. Nguyen; Ankita Naithani; Daniel Hurley; Li Bai; Farid El Garch; Frédérique Woehrlé; Christine Miossec; Benjamin Roques; Peadar O'Gaora; James L. Bono; Séamus Fanning (MDPI AG, 2021)
An antibiotic susceptibility monitoring programme was conducted from 2004 to 2010, resulting in a collection of 143 Escherichia coli cultured from bovine faecal samples (diarrhoea) and milk-aliquots (mastitis). The isolates were subjected to whole-genome sequencing and were distributed in phylogroups A, B1, B2, C, D, E, and G with no correlation for particular genotypes with pathotypes. In fact, the population structure showed that the strains belonging to the different phylogroups matched broadly to ST complexes; however, the isolates are randomly associated with the diseases, highlighting the necessity to investigate the virulence factors more accurately in order to identify the mechanisms by which they cause disease. The antimicrobial resistance was assessed phenotypically, confirming the genomic prediction on three isolates that were resistant to colistin, although one isolate was positive for the presence of the gene mcr-1 but susceptible to colistin. To further characterise the genomic context, the four strains were sequenced by using a single-molecule long read approach. Genetic analyses indicated that these four isolates harboured complex and diverse plasmids encoding not only antibiotic resistant genes (including mcr-1 and bla) but also virulence genes (siderophore, ColV, T4SS). A detailed description of the plasmids of these four E. coli strains, which are linked to bovine mastitis and diarrhoea, is presented for the first time along with the characterisation of the predicted antibiotic resistance genes. The study highlighted the diversity of incompatibility types encoding complex antibiotic resistance elements such as Tn6330, ISEcp1, Tn6029, and IS5075. The mcr-1 resistance determinant was identified in IncHI2 plasmids pCFS3273-1 and pCFS3292-1, thus providing some of the earliest examples of mcr-1 reported in Europe, and these sequences may be a representative of the early mcr-1 plasmidome characterisation in the EU/EEA.